Bahaya Mengendarai Kendaraan di Jalan Raya Bagi Anak di Bawah Umur - Febrina Hertika Rani; Ismail Pettanasse; Dea Justicia Ardha; Abdul Jafar; Sarah; Heni Marlina; Syahriati Fakhriah (CV. Doki Course and Training, 2024)
The phenomenon of motorbike riding among minors is increasingly widespread both in cities and villages. Many teenagers under the age of 17 pass by on motorbikes every day. The reasons for riding a motorbike vary, they are influenced by internal and external factors of the rider. Internal factors that influence the child include self-motivation to be able to ride a motorbike, while external factors are influenced by friends who can generally ride motorbikes, the relatively far distance from home to school, and parents who have given permission to them to ride motorbikes. Various policies have been implemented to tackle the problem of underage motorbike riders. Several ways to overcome this problem include enforcing laws related to driving regulations, providing mobility and accessibility for all citizens in a safe and environmentally friendly manner, giving an appeal to parents to always guide and supervise their children in terms of driving restrictions and provide knowledge about traffic signs and the dangers of driving a vehicle on the road to children.